Investigation of Chinese Students Majoring in Occupational and Physical Therapy on Attitude of Evidence-Based Practice - Bobbi GREINER; Keli MU; Angela PATTERSON; Margaret SCHUMACHER; Yonyue QI; Huiling HU; Yue XIAO; Yonghong YANG; Fanyuan MENG; Xiaodang LIU; Ya QUI (康复学报)
Objective:To examine the attitudes of students majoring in occupational therapy (OT) and physical therapy (PT) on evidence-based practice (EBP) and the possible impact of professional education in China.Methods:A cross-sectional survey of the Evidence-Based Practice Process Assessment Scale (EBPPAS) was administered to OT and PT students from four universities in China.Results:The total mean score of the students’attitudes toward all EBP subscales which included familiarity, attitude, intention, and engagement was 3.18 on a 5-point Likert scale. Significant differences in overall attitude were found between 2nd& 3rdyear students and 1styear and 4thyear students indicating professional education may have impact on students’attitudes (P=0.031 and P<0.001 respectively). No significant differences were found on the students’perceptions of EBP between OT and PT programs.Conclusion:Chinese OT and PT students both had positive attitudes toward EBP generally. Students’perceptions of EBP tended to improve throughout professional education which suggested the importance of EBP in the professional education of OT and PT.